Rozłóż na czynniki, wyłączając wspólny czynnik przed nawias:
a) 3(x-2)+y(x-2)=
b) 2a(2x-1)-b(2x-1)=
c) 2x(4a+3b)+3y(4a+3b)+(4a+3b)=
d) 3(x+2)²+(x+2)(2x-1)-(x+2)=
e) 4(a-b)(a+b)+(a-b)=
f) 2(a-b)²-(a-b)(a+b)=
g) x(a+b+c)-y(a+b+c)+z(a+b+c)=
h) (a+b)³-a(a+b)²=
i) x+y-(x+y)²=
Rozpiszcie się :)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-02T18:08:42+01:00
A
( x - 2 )( 3 + y )
b
( 2x - 1 )(2a - b)
c
( 4a + 3b)( 2x + 3y + 1)
d
( x + 2 )( 3x + 6 + 2x - 1 - 1 ) = ( x + 2 )( 5x + 4)
e
( a - b)( 4a + 4b + 1)
f
( a - b)( 2a - 2b - a - b ) = ( a - b)( a - 3b)
g
( a + b + c)( x - y + z)
h
( a + b)²(1 - a)
i
( x+ y)( 1 - x + y)
3 3 3